2016
DOI: 10.1002/jmrs.183
|View full text |Cite
|
Sign up to set email alerts
|

Assessing feasibility, compliance and toxicity of concomitant chemo-radiotherapy in head and neck cancers in the Northern Territory: initial experience and challenges

Abstract: IntroductionComprehensive oncology services have recently been introduced in the Northern Territory (NT) enabling delivery of concurrent chemo‐radiotherapy (CCRT) in locally advanced head and neck squamous cell carcinoma (LAHNSC). The purpose of this study is to assess feasibility, compliance and toxicity of CCRT in remote Australia.MethodsChart review was conducted for all patients >18 years, with biopsy‐proven LAHNSC, receiving curative intent CCRT between January 2010 and September 2012.ResultsThe study pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A significant improvement in disease-free and locoregional recurrence-free survival rate has been observed; the survival rate has been reported to be around 50 -60% at 5 years [11,12]. However, symptoms of grade 2, 3 and even grade 4 toxicity (such as rash, fatigue, neuropathy, anemia, alopecia, myelosuppression, neutropenia, mucositis, immunosuppression, xerostomia, hypothyroidism, diarrhea, and constipation) have been observed in different clinical studies with systemic chemotherapy [13][14][15][16]. A recent study has reported certain changes in gut microbiota leading to clostridium difficile infection (CDI) in head and neck cancer patients who received systemic paclitaxel chemotherapy followed by radiation [17].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…A significant improvement in disease-free and locoregional recurrence-free survival rate has been observed; the survival rate has been reported to be around 50 -60% at 5 years [11,12]. However, symptoms of grade 2, 3 and even grade 4 toxicity (such as rash, fatigue, neuropathy, anemia, alopecia, myelosuppression, neutropenia, mucositis, immunosuppression, xerostomia, hypothyroidism, diarrhea, and constipation) have been observed in different clinical studies with systemic chemotherapy [13][14][15][16]. A recent study has reported certain changes in gut microbiota leading to clostridium difficile infection (CDI) in head and neck cancer patients who received systemic paclitaxel chemotherapy followed by radiation [17].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…IV-infused Taxol (which also contains ethanol) has been shown to cause Grade I–Grade IV toxicity in the majority of patients who received it. , Currently, chemoradiation (concurrent/sequential chemotherapy–radiotherapy combination (CT–RT)) is the standard treatment for patients with inoperable/locally advanced cancer because this combination produces benefits in terms of tumor response and overall survival relative to either alone . Unfortunately, however, using chemotherapeutic drugs on top of radiation significantly increases side effects, resulting in a progressive worsening of the quality of life for patients. The seriousness of side effects of conventional chemoradiation (CT–RT) raises a need for tumor-specific radiosensitization.…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is a significant public health problem in many countries [1] and is the most common malignant neoplasia of the oral cavity [1]. Alcohol and tobacco consumption are the most critical risk factors currently described for OSCC [2]. However, individual intrinsic factors also play a significant role in the development and prognosis of cancer [3][4][5].…”
Section: Introductionmentioning
confidence: 99%